The modified peakedness as a M|G|∞ busy cycle distribution characterizing parameter - Ferreira, Manuel Alberto M. (2015)
It is exposed that a parameter, then called ߠ,similar to the parameter ߟ proposed in (1) to characterize the ܯ|ܩ|∞ queue busy period distribution, that is a modification of the peakedness proposed in (2) is also useful to characterize the M/G/∞ queue busy cycle distribution.